Exploring relevant features of colorectal cancer from clinical and biological data : a bioinformatics approach - Vieira, Lucas Maciel (2023)
Tese (Doutorado) — Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Ciência da Computação, 2023.